Trithiocyanurate complexes of iron, manganese and nickel and their anticholinesterase activity - Kopel, Pavel; Dolezal, Karel; Langer, Vratislav; Jun, Daniel; Adam, Vojtech; Kuca, Kamil; Kizek, Rene (Molecules (Basel, Switzerland), 2014)
The complexes of Fe(II), Mn(II) and Ni(II) with a combination of a Schiff base, nitrogen-donor ligand or macrocyclic ligand and trithiocyanuric acid (ttcH3) were prepared and characterized by elemental analysis and spectroscopies. Crystal and molecular structures of the iron complex of composition [Fe(L1)](ttcH2)(ClO4)·EtOH·H2O (1), where L1 is Schiff base derived from tris(2-aminoethyl)amine and 2-pyridinecarboxaldehyde, were solved. It was found that the Schiff base is coordinated to the central iron atom by six nitrogens forming deformed octahedral arrangement, whereas trithiocyanurate(1-) anion, perchlorate and solvent molecules are not coordinated. The X-ray structure of the Schiff base sodium salt is also presented and compared with the iron complex. The anticholinesterase activity of the complexes was also studied.
Keywords: Iron; triaziny; mangan; Cholinesterase Inhibitors; cholinesterasy; Rats; enzymatické testy; Brain; pyridiny; Nickel; Schiffovy báze; Animals; nikl; Crystallography, X-Ray; Schiff Bases; Ethylenediamines; zvířata; ligandy; Coordination Complexes; Pyridines; mozek; Enzyme Assays; železo; komplexní směsi; krysa rodu Rattus; Triazines; Manganese; komplexní sloučeniny; cholinesterasové inhibitory; ethylendiaminy; Complex Mixtures; Cholinesterases; Ligands; krystalografie rentgenová